The role of context in transactional English: spoken utterances and public signs in the UAE - Lanteigne, Betty; Najafi, Hedieh (Frontiers in Communication, 2024)
Transactional and interactional English communications tend to be on a continuum rather than a dichotomy, with some communications having characteristics of both, yet others tending more toward one type of communication or the other. In general, written communication tends to be more informative (transactional) than spoken communication, which tends to include more interactional communication. Using insights from geosemiotics and linguistic analysis, this study analyzed spoken English-as-a-lingua-franca (ELF) communication observed in Dubai/Sharjah and written communication in public signs in Al Ain, looking at how contextual influences play a role in facilitating hearer/reader understanding of the meaning being communicated. From identified ELF communications in Dubai/Sharjah (from Lanteigne, 2017; Parra-Guinaldo and Lanteigne, 2021) and photographed public signs with English text in Al Ain (from Najafi, Lanteigne, and Husni, submitted) in the UAE, ten spoken and eight written instances of transactional English were selected to be analyzed in terms of patterns in the role of context in hearer/reader understanding of intended meaning. Comparing/contrasting contextualization of these spoken and written transactional English communications revealed the influence of the context on hearer/reader awareness of spatio-temporal aspects, background schemata (social/societal, cultural, economic, and religious aspects), prior communications, and ELF mutual accommodation of meaning in terms of understanding and interpreting intended meaning, as well as identifying aspects of contextualization common to both spoken and written transactional English.